Widespread Occurrence of a CYP51A Pseudogene in Calonectria pseudonaviculata. Issue 1 (2nd January 2020) - Stravoravdis, Stefanos; LeBlanc, Nicholas R.; Marra, Robert E.; Crouch, Jo Anne; Hulvey, Jonathan P.
Abstract: Calonectria pseudonaviculata and C . henricotiae are two closely related fungal species responsible for boxwood blight disease of ornamental shrubs ( Buxus spp.) in the U.S. and Europe. A previous study has shown isolates of the latter species, which is restricted to Europe, to be less sensitive to tetraconazole, an azole fungicide. In this study, we have analyzed the CYP51 paralogs for polymorphism in 26 genomes, representing geographically disparate populations of C . pseudonaviculata ( n  = 19) and C . henricotiae ( n  = 7), from the U.S., Europe, Asia, and New Zealand. The presence of a CYP51A pseudogene and lack of a functional CYP51A paralog in all C . pseudonaviculata genomes examined is a novel discovery for fungi and could have implications for the evolution of resistance to antifungal chemicals.